Legal Regulation of the Digital Transformation of Local Self-Government in the BRICS Countries - M. Lipchanskaya; S. Channov; A. Churikova (BRICS Law Journal, 2024)
This article presents an analysis of strategies used for the legal regulation of digital transformation processes at the municipal level in the BRICS countries. A systematic analysis of modern trends in the legal regulation of digital transformation in Brazil, South Africa, India and China was carried out, and the features and general directions of this process were highlighted. The authors noted a variety of different approaches to normalizing digital processes in management, ranging from fixing basic principles at the constitutional level to developing “flexible” regulation constitutionally mandated through by-laws and state political and legal documents. It is shown that the digitalization of public administration is primarily focused on the level of national government, since financial resources are specifically concentrated at the highest level of governance. It is concluded that the specificity of local government, manifested in a high degree of self-government and participation of the population in solving life support issues, objectively requires a shift in the emphasis of digitalization to the local level of government. It has been proven that this process requires strategic state planning on the part of the state for the digitalization of local self-government, taking into account the elimination of the “digital divide” in municipalities. The authors propose the implementation and development of the “smart city” concept in the BRICS countries with a differentiated scale of digitalization criteria for the various municipalities.